Membangun Simulasi Jaringan LAN Sederhana Menggunakan Packet Tracer - Adinugroho, Rizki Indrasetyawan (Siscode, 2013)
Packet tracer is aprogram to make a computer network simulation. To make a network need design and a planning. It is necessary to make a simulation so the network that build can be good to work, minimalize an error in build of LAN network. Making a network use a device like : two pieces ofÂ  switch, 11 wires of UTP with straight wiring, one wire of UTP with cross wiring, 10 computer as a client and one pieces of printer. To combine 2 switch need a wire of cross so can avoid a crash of data or in the other word call crash each other. A computer that will use as a client is setting with straight wiring and an other computer is setting with switch that have been combine before. A printer combine to switch with straight wiring too. The first switch have 5 computers as a client, second switch have 5 computers and one printer. One computer of client use one wire like a configuration of star topology. The indicator will be a green light if all device are setting ofÂ  right, after that setting IP address to computer of client where each computer have a different of IP address. To test that all of device are setting an IP address ping the computer client to know is a computers have been configurated or notyet. In the command prompt will write of ârepleyâ if the computer have been configurated. This research produce of simulation computer network that using a star topology. Keyword :simulation, LAN network, packet tracer